Constructive Empiricism and Logical Positivism: The Return of the Prodigal Son - van der Merwe, Ragnar (Filozofia Nauki, 2023)
Bas van Fraassen’s Constructive Empiricism (CE) has been much discussed, but there is a curious feature of van Fraassen’s writings that has been overlooked up until now: he sometimes capitalizes certain key terms, notably “Induction.” This is done to differentiate pragmatic small ‘i’ induction (which has epistemic import) from rule-bound capital ‘I’ induction (which does not). In this paper, I argue that van Fraassen’s small letter / capital letter distinction reveals an underlying dualism that is reminiscent of the notoriously problematic semantic dualism in Logical Positivism (between a theoretical language and an observational language). Despite partly developing CE to overcome Logical Positivism’s kind of dualism, van Fraassen seems to have tacitly endorsed it anyway. If so, then CE requires revision, but it is not clear how to do so or what the way forward should be once CE is understood as innately dualistic.